Segmental Variations in Fish Consumption Behaviour: A Case Study of Sonitpur District of Assam - Goswami, Chandan; Bhuyan, Pradip C. (Indian Journal of Marketing, 2012)
The study was carried out in Sonitpur district of Assam to find out the segmental variation of fish consumption patterns based on demographic and geographic profiles. A total of 132 respondents covering four different communities from both rural and urban areas had been selected following quota and judgment sampling. The study revealed that the per-capita consumption of fish in the study area was 13.22 kg. Among different communities, the per-capita consumption of fish was found to be the highest among the Assamese (16.2 kg) community. The study clearly indicates that fish consumption increases with an increase of family income. The average monthly expenditure on fish over total expenditure of food items varied from 12.22% to 17.56% among different communities and 11.63% to 23.12% among different income groups. Among different factors influencing fish consumption, palatable taste of the fish was the first reason followed by high nutritive value, easy digestibility, less fat content and easy availability of fish in comparison to meat at an affordable price. Based on the findings of the study, the production and consumption gap of fish in the district was estimated and some strategies for improvement of fish production and marketing have been developed.